WOMEN RESISTANCE IN EKA KURNIAWAN’S CORAT-CORET DI TOILET SHORT STORY COMPILATION BOOK - Asri Furoidah (PARADIGM: Journal of Language and Literary Studies, 2019)
Eka Kurniawan's Corat-coret di Toilet short stories compilation book contains twelve short stories that tell about light stories everyday but full of social criticism. Some of the short stories that portrayed female characters presented women who were not free in their lives, one of which was titled Dongeng Sebelum Bercinta and Si Cantik yang Tak Boleh Keluar Malam. Therefore, this study aims to analyze the position of women and their resistance toward patriarchal domination. This is interesting to be studied further by using feminist theory to find the position of women in literary works written by male writers. This research will focus on the actions of female characters which shape their position in the story. The data used in this study are in the form of words, sentences or expressions from short stories that show the dominance of patriarchy towards women and their efforts to get out of domination. From research using feminist theory it was found that patriarchal domination arises in the closest male characters to female characters such as fathers, male friends and husbands. Women resistance in the story was a form of false resistance which in turn strengthened the dominance of patriarchy and the dichotomy between men and women. This was found based on the fact that every resistance made by women turned to weaken women themselves.